1990
DOI: 10.1002/bbpc.19900941010
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogenated Amorphous Silicon by Infrared Multiphoton Absorption with a Pulsed CO2‐Laser

Abstract: The following work gives a discussion on hydrogenated amorphous silicon (a‐Si:H) film preparation by laser induced chemical vapor deposition (LICVD) using a pulsed CO2‐laser in a parallel configuration. Deposition rate and initiation of polymerization were studied as a function of total pressure, gas flow, gas mixture (buffer gas, silane and/or disilane), substrate temperature, and radiation flux. The results lead to a reaction model where higher silane homologues play an important role for the film production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Mechanistically, SiH 2 is known to be a primary decomposition product in the decomposition of silanes. The interaction of the SiH 2 radical with Si 2 H 6 is a subject of interest in the present work because Si 2 H 6 is one of the most commonly employed reagents and silylene is known to be a very reactive diradical that inserts into Si–H bonds very efficiently, forming excited adduct Si 3 H 8 . The excited adduct can dissociate via intramolecular 1,2-H shifts, producing various products. Inoue et al detected SiH 2 by laser-induced fluorescence and found the rate constants of the SiH 2 reaction with Si 2 H 6 to be 5.7 × 10 –10 cm 3 molecule –1 s –1 in 1 Torr of helium at room temperature. Later, Jasinski et al generated SiH 2 by using laser absorption spectroscopy and found the overall rate constant of the SiH 2 with disilane reaction from 1 to 10 Torr of He pressure at 298 K; the rate constant measured at 1 Torr of pressure was 1.5 × 10 –10 cm 3 molecule –1 s –1 .…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mechanistically, SiH 2 is known to be a primary decomposition product in the decomposition of silanes. The interaction of the SiH 2 radical with Si 2 H 6 is a subject of interest in the present work because Si 2 H 6 is one of the most commonly employed reagents and silylene is known to be a very reactive diradical that inserts into Si–H bonds very efficiently, forming excited adduct Si 3 H 8 . The excited adduct can dissociate via intramolecular 1,2-H shifts, producing various products. Inoue et al detected SiH 2 by laser-induced fluorescence and found the rate constants of the SiH 2 reaction with Si 2 H 6 to be 5.7 × 10 –10 cm 3 molecule –1 s –1 in 1 Torr of helium at room temperature. Later, Jasinski et al generated SiH 2 by using laser absorption spectroscopy and found the overall rate constant of the SiH 2 with disilane reaction from 1 to 10 Torr of He pressure at 298 K; the rate constant measured at 1 Torr of pressure was 1.5 × 10 –10 cm 3 molecule –1 s –1 .…”
Section: Introductionmentioning
confidence: 98%
“…Roth et al investigated the gasphase parameters such as the flow, temperature, and pressure of participating reactants; the energy input for dissociation reactions, the size, and the structure of Si−H compounds have an important influence on the properties of the surface layer. 13 Mechanistically, SiH 2 is known to be a primary decomposition product in the decomposition of silanes. 1−19 The interaction of the SiH 2 radical with Si 2 H 6 is a subject of interest in the present work because Si 2 H 6 is one of the most commonly employed reagents and silylene is known to be a very reactive diradical that inserts into Si−H bonds very efficiently, forming excited adduct Si 3 H 8 .…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation